Transforming Gender Norms in Tanzania: Empowering Women Farmers - CGIAR (CGIAR, 2025)
Women cassava farmers in Tanzania share their experiences facing restrictive gender norms contributing to development challenges. They highlight issues such as limited access to loans and ownership of agricultural land. Devis Mwakanyamale, Research Associate at IITA Tanzania, explains how the CGIAR Initiative on Gender Equality, HER+ -TRANSFORM work package collaborates with partners to design gender transformative interventions to reduce these normative constraints. Geraldina Mushema from a partner organization provides insights into the co-design process of these interventions and the benefits of the approach.